(untitled) (Journal of Informatics Education and Research, 2025)
Rapid and sudden shifts in the outside world may cause crises for businesses that can turn out of reach. In several nations, the Covid-19 pandemic has resulted in severe economic harm and people’s suffering. The effectiveness of a company is greatly influenced by HR management, and both these fields must be combined. This study examines the function of HR management in handling crisis operations and discovers a link between the inefficiency of HRM methods and company crisis management. In the era of shifting circumstances, modern businesses face risks in managing their human resources, including unsuccessful hiring, abrupt departures, and the loss of important technical personnel. These hazards have the potential to disrupt businesses’ regular operations and, in the event of a severe issue, even result in fatalities. To avoid human resources threats and investigate risks identified and prevented in HR management, it is critical to create a feeling of risk. This study presents corporate human resources avoiding risk techniques and reaction strategies after elaborating on the notion of internal HR risk and features and risk recognition analysis. Overcoming the difficulties that businesses have in handling crises requires a shift in conceptual and business study.